Evaluation of the quality of women living with HIV's life - Michele Teixeira; Maely Terezinha Mendes; Kátia Pereira Borba; Evani Marques Pereira; Evandro de Borba (Universidade Federal de Santa Maria, 2015)
Aim: to evaluate the quality of women living women with HIV's life. Method: cross-sectional descriptive study with quantitative approach performed in a clinic specialized in rendering services to people living with HIV, through the application of WHOQOL- HIV BREF questionnaire. Results: from the 41 women who participated in this study, 37 claimed having contracted HIV through heterosexual intercourse. The scores of social relations and environment domains showed similar values. Among the domains of quality of life, social relationships obtained the highest score (15,1), followed by the environment (15,0), spirituality (14,8) and independence level (14,4). Lower scores were achieved in the areas of psychological (13,8) and physical (13,6). Final Remarks: it is believed that the quality of women living with HIV's life was influenced by the impact of the diagnosis. It stresses the importance in conducting other studies involving this issue, in order to collaborate for the improvement of assistance to this clientele